PENGEMBANGAN MODUL BIOLOGI MODEL PEMBELAJARAN DISCOVERY LEARNING PADA MATERI SISTEM ORGANISASI KEHIDUPAN KELAS VII - Maria Fatima Neno; Yohanes Bare; Yohanes Boli Tematan (Jurnal Biogenerasi, 2022)
The Discovery learning model leads students to find their own concepts by providing problems to be solved. This study aims to analyze the validity and feasibility of the biology module of the discovery learning model on the material of life organization system in seventh-grade junior high school. The research method is Research and Development with a 4-D model. The study results show that the biology module of the discovery learning model on the material of living organization systems developed has a material validator validity value of 79.9 and is very valid by a language validator of 88, and from a media validator of 84.2. The small-scale module feasibility questionnaire by educators obtained an average score of 102, and the feasibility by students scored 101.5, where the value was categorized as very feasible to use, while the large-scale feasibility questionnaire by educators had a score of 105 and the feasibility questionnaire by students had a score of 104.65 categorized as very proper to use.